Evaluation of the Content and Structure of Otorhinolaryngology Curricula in Libyan Medical Faculties’ Undergraduate Program from 2023-2024 - Abir Sharif (AlQalam Journal of Medical and Applied Sciences, 2024)
This study conducted to evaluate the content and structure of Otorhinolaryngology (ORL) curricula in Undergraduate Medical Education (UME) program in all Libyan medical faculties through surveying the stuff member of the subject. A cross section study conducted from October 2023 to early of January 2024, using structural questionnaire, consisted of 18 questions, [13 closed and 5 opened], administered to stuff members in Libyan medical faculties, 32 out of 52 faculty members completed the survey in (Tripoli, Zawia, Misurata, Sabratha, Benghazi, Omer Elmoukhtar, Alasmarya, Elmergib, Sabha, Tobrouk) medical faculties, other faculties not respond. Respondents represented diverse geographic institutions, lending broader perspectives. The predominant teaching modality was power point lectures were (84.4%), with limited interactive techniques like case-based learning (6.3%), didactic large group lectures (56.3%) were more common than clinical bedside teaching (28.1%). In addition, faculty members expressed concerns on the curriculum is inadequately developing student knowledge (43.3%) and skills (60%), with insufficient teaching hours (62.5%) and suboptimal assessment methods (56.6%). While 57.7% of respondent support establishing separate departmental status for otorhinolaryngology and head/neck specialties from general surgery. This study highlights the necessary to implement a curriculum that includes clinical training alongside standardized lectures and to update the evaluation methods as well as ensure a comprehensive and fair exposure to otorhinolaryngology. أجريت هذه الدراسة لتقييم محتوى وهيكل مناهج جراحة الأنف والأذن والحنجرة في برنامج البكالوريوس في جميع الكليات الطبية الليبية من خلال دراسة مسحية مقطعية أجريت في الفترة من أكتوبر 2023 إلى أوائل يناير 2024 ، باستخدام استبانه الكترونية استهدفت أعضاء هيئة تدريس مادة جراحة الأنف والأذن والحنجرة في كليات الطب الليبية ، أستجاب 32 من أصل 52 عضو هيئة تدريس في كليات الطب البشري التالية (طرابلس ، الزاوية ، مصراتة ، صبراتة ، بنغازي ، عمر المختار ، الأسمرية ، المرقب ، سبها ، طبرق) ، الكليات الأخرى لم تستجيب. مثل المستجيبون مؤسسات جغرافية متنوعة، مما قدم وجهات نظر أوسع. كانت محاضرات العرض التقديمي هي طريقة التدريس السائدة (84.4٪)، مع استخدام محدود للتقنيات التفاعلية مثل التعلم القائم على الحالة CBL والتعلم القائم على الفريق TBL (6.3٪)، كما كانت محاضرات المجموعة التعليمية الكبيرة هي الأكثر شيوعا بنسبة (56.3٪) بينما التدريس السريري (28.1٪). علاوة على ذلك، أعرب أعضاء هيئة التدريس عن مخاوفهم بشأن عدم تطوير وتحديث المنهج الدراسي دوريا بشكل يمد الطلاب بالمعرفة الكافية (43.3٪ تقييمات سلبية) ولا بالمهارات اللازمة (60٪ سلبية)، مع عدم كفاية ساعات التدريس (62.5٪) وطرق التقييم دون المستوى (56.6٪). مما رجح فصل منهج مادة جراحة الأنف والأذن والحنجرة وجراحة والرأس / الرقبة عن تخصص الجراحة العامة بنسبة (57.7٪ إيجابي). تسلط هذه الدراسة الضوء على ضرورة تطوير منهج جراحة الأنف والاذن والحنجرة بحيث يتضمن التدريب السريري بالإضافة الي المحاضرات مع تحديث طرق التقييم بشقيه النوعي والكمي، وكذلك ضمان التعرض العادل والشامل للطلاب لهذا التخصص اثناء مرحلة التعليم الطبي الجامعي.